ESTUDIO QUÍMICO DE LOS TALLOS DE CINCHONA PUBESCENS - Loayza O y Cols., Karin (2019)
From the stems of the Cinchona pubescens, wich were collected in the locality Yuracmallo (Province of Sandia, Puno), quinine was obtained, wich was identified by the mass spectra, RMN1H, RMN13C y 1H-1H COSY. Furthermore, the qualitative analysis of the secondary metabolites was done.